The Applications of Nanopore Sequencing Technology in Pathogenic Microorganism Detection - Xiaojian Zhu; Shanshan Yan; Fenghua Yuan; Shaogui Wan (Canadian Journal of Infectious Diseases and Medical Microbiology)
Infectious diseases are major threats to human health and lead to a serious public health burden. The emergence of new pathogens and the mutation of known pathogens challenge our ability to diagnose and control infectious diseases. Nanopore sequencing technology exhibited versatile applications in pathogenic microorganism detection due to its flexible data throughput. This review article introduced the applications of nanopore sequencing in clinical microbiology and infectious diseases management, including the monitoring of emerging infectious diseases outbreak, identification of pathogen drug resistance, and disease-related microbial communities characterization.